Efektivitas Pelajaran PAI, Budi Pekerti, dan Aswaja dalam Pembentukan Karakter Siswa SMA Nur Lintang Kedu - Yusuf, Achmad; Khilia Diana, Rosy (Jurnal Pengabdian Kepada Masyarakat, 2025)
Field Experience Practice (PPL) is an obligatory extracurricular activity for prospective teacher studentsas a form of applying theory into real practice in schools. This article discusses the implementation of PPL forstudents of the Islamic Education Program (PAI) at Sekolah Tinggi Islam Kendal (STIK) at SMA Nur LintangKedu Temanggung in 2025. The purpose of PPL is to provide factual experience in teaching and educationaladministration activities, improve the professional competence of prospective teachers, and strengthen therelationship between Higher Education Institutions (LPTK) and partner schools. The research uses a descriptivequalitative approach with the documentation method from the PPL report.The results show that PPL is carried out through stages of training, observation, teaching practice, andschool administration. Students face challenges such as limited LCD equipment, lack of student discipline, andchallenges in classroom management. Problem-solving is carried out through the use of alternative media,discipline habituation, and improved communication with supervising teachers. In conclusion, PPL contributessignificantly to equipping students to become professional educators while also providing positive impacts forpartner schools.